األفؼال انكالييت اإلَجازيت في ٔصايا نقًاٌ حكيى النبُّ (دراست تحهيهيت تذأنيت في سٕرة نقًاٌ األيت 21 - 19( - Lailatul Jamila; Ahmad Effendi (Tafhim Al-'Ilmi, 2021)
Pragmatic studies have an important role in language learning, as it is seen as the study of the useof language in communicative contexts such as recognizing communicated messages or speech actsthat are being spoken. One of the main topics in pragmatic studies is speech act. Speech act is apragmatic feature that connects actions with the language used. In other words, speech act theoryattempts to explain how speakers use language to achieve the goal of action and how speechpartners infer their intended meaning so as to shape what is said (Altikriti, 2011). This study aimsto describe the form of illocutionary speech acts on Luqman’s educational testament for his son .This research is a type of qualitative description research. The data source in this study is theutterances uttered by Luqman verses 12-19 contain the story of Luqman and the speech spoken byLuqman to his son.. Based on data analysis, the conclusion can be drawn. that the forms ofillocutionary speech acts found were directive, declarative, expressive, and assertive.Keywords : pragmatics, speech act, illocutionary, Luqman verses (12-19